Struktur Dan Makna Lagu Balasan Sang Qadli Pada Grup Annida Nirwana Di Jl. KHZ. Mustafa Kecamatan Sukarame Kabupaten Tasikmalaya - Salsabila Rahayu; Denden Setiaji; Asti Tri Lestari (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study, entitled "The Structure and Meaning of the Song Balasan Sang Qadli in the Annida Nirwana Group," aims to analyze the lyrical structure and meaning contained in the song. This study uses a descriptive qualitative approach with a semiotic analysis method to examine the meaning of the lyrics based on Ferdinand de Saussure's theory. Data collection techniques were carried out through observation, interviews, and documentation, with the main subjects of the study being the composer of the song Balasan Sang Qadli and related parties in the Annida Nirwana group. The results show that the lyrical structure in this song has a pattern of repetition and religious diction that strengthens its spiritual message. The meaning of this song depicts a reflection of human life before God, regret for sin, and an invitation to improve oneself by approaching Allah SWT. The symbols used in the lyrics strengthen the religious and da'wah nuances in the song. In conclusion, the song Balasan Sang Qadli functions not only as entertainment, but also as a da'wah medium that conveys Islamic values ​​through modern qasidah music. This research is expected to contribute to the study of religious music and enrich understanding of the role of qasidah in Islamic da'wah.